Interface dipole evolution from the hybrid coupling between nitrogen-doped carbon quantum dots and polyethylenimine featuring the electron transport thin layer at Al/Si interfaces - Sasimontra Timjan; Ta-Cheng Wei; Kuan-Han Lin; Yi-Ting Li; Po-Hsuan Hsiao; Chia-Yun Chen (Applied Surface Science Advances)
The assessment of electron transport layer (ETL) for rear-contact engineering of silicon (Si) based optoelectronics has been considered as one of the critical challenges that leverage the performance improvement and device reliability. In this work, the hybrid design of ETL, obtained from the solution-processed nitrogen-doped carbon quantum dots (NCQDs) incorporated with organic polyethylenimine (PEI) demonstrates the feasible contact characteristics for the modification of Si/Al contacts, which greatly facilitates the transport and collection of photoexcited electrons in the Si-based optoelectronics. The aspects of microstructures, functional groups, chemical features, interfacial characteristics and band structures of NCQD/PEI are explicated, visualizing that the evolution of interface dipoles mediated by the overall outcome of physisorption and chemisorption effects, modifies the surface potential difference and results in the explicit reduction of the Al work function from 4.3 eV for pristine Al to 3.23 eV based on the optimized constitutional design (0.10 % NCQD in PEI). These findings are practically employed on the Si-based hybrid solar cells at Si/Al interfaces, fulfilling the conversion-efficiency improvement by 30.9 % compared with reference cells without ETL employment, which are experimentally interpreted by the efficient electron transport across the Si/Al heterojunction and charge collection.